#GetFit : examining the roles of online health information behaviors and eHealth literacy on Filipinos’ dietary and fitness behaviors - Cayabyab, Ysa Marie Therese Macaraeg (2018)
Objectives: In current society, there has been a shift in the healthcare landscape as digital revolution propels the use of Internet-based technologies for health communication. In the Philippines, Internet use for health has recently become more prevalent with the salience of online content related to well-balanced diet and physical exercise. While previous studies have mainly investigated the combined influence of traditional, mediated, and online information sources on health, this study exclusively focused on web-based sources to provide an overall look at the extent of influence of online sources. Specifically, it examined the influence of online health information behaviors (active and passive OHIBs) and eHealth literacy on one’s performance of dietary and exercise behaviors. Methods: Utilizing an expanded model of the Theory of Planned Behavior (TPB), a panel survey was conducted among Filipino young adults aged 18-29 years old. The sample (N=352) was drawn from a university population in the Philippines. Path analysis was used to examine the direct and indirect effects between variables. Results: While passive OHIB occurred more frequently than active OHIB, only active OHIB significantly predicted intention for both health behaviors. Attitudes, subjective norms, and perceived behavioral control mediated the effects of active OHIB on intention. eHealth literacy also influenced one’s intention to physically exercise, but only when mediated by subjective norms. Consistent with TPB’s main assertion, intention led to action for both health behaviors. Conclusion: Findings suggest that online media use corresponds to health behavior only to the extent that there is a deliberate search for health information. The mediation effects of subjective norms also reflect how health-related online contents influence perceptions of normative behaviors, which consequently lead to the performance of exercise behavior. The findings also present a gap between knowledge and behavior as eHealth literacy did not completely translate to health behaviors, despite the relatively high eHealth literacy scores of the study participants. Overall, the study’s extension of the TPB model increased the variance explained for healthy eating and physical exercising behaviors. This provides empirical evidence that supports the pathway of relationship among online information, psychosocial predictors, and behaviors.